Platelet G i protein Gα i2 is an essential mediator of thrombo-inflammatory organ damage in mice - Devanathan, Vasudharani (2015)
Platelets are crucial for hemostasis and thrombosis and exacerbate tissue injury following ischemia and reperfusion. Important regulators of platelet function are G proteins controlled by seven transmembrane receptors. The Gi protein Gα(i2) mediates platelet activation in vitro, but its in vivo role in hemostasis, arterial thrombosis, and postischemic infarct progression remains to be determined. Here we show that mice lacking Gα(i2) exhibit prolonged tail-bleeding times and markedly impaired thrombus formation and stability in different models of arterial thrombosis. We thus generated mice selectively lacking Gα(i2) in megakaryocytes and platelets (Gna(i2)(fl/fl)/PF4-Cre mice) and found bleeding defects comparable to those in global Gα(i2)-deficient mice. To examine the impact of platelet Gα(i2) in postischemic thrombo-inflammatory infarct progression, Gna(i2)(fl/fl)/PF4-Cre mice were subjected to experimental models of cerebral and myocardial ischemia/reperfusion injury. In the model of transient middle cerebral artery occlusion stroke Gna(i2)(fl/fl)/PF4-Cre mice developed significantly smaller brain infarcts and fewer neurological deficits than littermate controls. Following myocardial ischemia, Gna(i2)(fl/fl)/PF4-Cre mice showed dramatically reduced reperfusion injury which correlated with diminished formation of the ADP-dependent platelet neutrophil complex. In conclusion, our data provide definitive evidence that platelet Gα(i2) not only controls hemostatic and thrombotic responses but also is critical for the development of ischemia/reperfusion injury in vivo.